Transparência Ativa: uma análise nos regimes próprios de previdência nos municípios do estado de Mato Grosso do Sul - GILMARCOS JACQUES DE LIMA (2022)
This study aims to analyze the level of active transparency (in electronic portals) of the Local Social Security Systems (RPPS) of municipalities in Mato Grosso do Sul. Thus, the premise this study was built on was based on the theory of agency and principles of good governance in the public sector, using the observations found in the RPPS Pro-Management Manual (2020), as well as the Law of Access to Information for the construction of the Indicator of Active Transparency of RPPS (RITA). The population of the present study is composed of 51 RPPS. Of that total, it was necessary to exclude five entities, bringing to 46 the number of RPPS that integrated the sample of this work. Evidence to measure the RITA was taken from the electronic portals of the RPPS or the electronic portals of municipal governments. When analyzing the variables that interfere with the RITA, this study was limited to researching the influence of the legal nature of RPPS and their period of operation, the insured population, municipal development, the average remuneration of the insured population, the dispatch of information to the Secretariat for Social Security (SPREV) and the regularity of the RPPS, in addition to their financial situation. It is an explanatory study of the applied, quantitative type, in addition to being a documental research with secondary data. In the first moment of the analysis, descriptive statistics were used to show the oscillations in each variable. In the second stage, multiple linear regression was applied, aiming to answer to the objective of this study. The results show that of the 46 RPPS analyzed, 10 RPPS did not have electronic portals for the disclosing information on their social security system, or even had their pages offline, 21 of them had RITA classified as critical or insufficient, and only 4 RPPS had the desired level of active transparency. However, none of the RPPS in the sample obtained the maximum score on the RITA. With these results in hand, the explanatory variables for the level of active transparency of the RPPS that composed this research were analyzed, with the intention of obtaining answers to the hypothesis raised. The findings showed that the RPPS established as an autarchy and the insured population exert a positive and significant influence on the level of active transparency. In addition, other determinants such as: municipal development, average remuneration of the insured population, the dispatch of information to the SPREV, regularity of the RPPS and the financial situation of the RPPS did not present significant effects to the point of accepting the formulated hypotheses (variables with a positive influence on active transparency). Even considering the complexity of the phenomenon that determines active transparency in RPPS, the model presented in this work revealed an explanatory power of 43,95%. The conclusions obtained are restricted to the RPPS and to the period analyzed, in addition to the static situation of data collection of the explanatory variables used, which constitutes a limitation. It is expected that the work will bring contributions aimed at social security managers, auditory bodies, as well as society as a whole. The contributions made in this study arise from the pretext that transparency, its indicators, and social participation tend to form a virtuous cycle, which complement and develop itself, and even more so with the active participation of society. And in this context, everyone wins: the RPPS gain transparency in scale and tend to raise the level of governance according to the RPPS Pro-Management Manual, accountability is promoted, and the legitimacy of managers is increased, in addition to fostering democratic spaces for social participation, as well as reducing conflicts of interest. In short, this study also made it possible to contribute with some insights for future studies, suggesting the application of a longitudinal study or even the inclusion of other explanatory variables for the level of active transparency of the RPPS.